EFFECT OF DIFFERENT FEEDS ON THE GROWTH AND SURVIVAL OF SNAKEHEAD FISH (Channa striata) SEEDS - aditya, Rendi; Mulyadi, Mulyadi; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in Agustus to September 2018 in the Aquatic Aquaculture Technology Laboratory of Marine Fishery University of Riau. The aims of this research was to determine the growth and survival rate of Channa striata with different feeds. This research used a size aquarium 40 x 30 x40 cm3 with a waterin hight 10 cm for 12 units. The feed used in the form of Pellet, Earthworms, Blood worm, and Tubifex sp. given with dose of 60% from the body weight of thefish. The method used in this research was the experimental method of Completely Randomized Design (CRD) using one factor with 4 treatments and 3 replications. The best treatment result is feeding with Tubifex sp which can produce absolute weight growth rate (1,48 gram), absolute length growth (3,7 cm), growth of specific length (5,45%) and survival rate (97,22%). Water quality during the research was obtained of pH 6.0-7.0, temperature 26-28 0C, DO 3,9-5,4 mg/L and ammonia 0,01-0,05 mg/L. The result of research with different feeding significantly affected the growth of Channa striata, but did not significantly affect the survival of Channa striata. Giving Tubifex sp. is the best feeding to increase the growth of Channa striata. Keywords : Tubifex sp, Channa striata, Growth and survival rate.